1961
DOI: 10.1084/jem.113.4.795
|View full text |Cite
|
Sign up to set email alerts
|

The Lathyrogenic Effect of Isonicotinic Acid Hydrazide (Inah) on the Chick Embryo and Its Reversal by Pyridoxal

Abstract: Evidence has been previously presented to show that lathyrogenic agents increase the solubility of collagen and the fragility of the connective tissues in the chick embryo (1). Assay systems for the detection of lathyrogenic agents have hitherto relied upon loss of weight and morphological changes in the rat as criteria of activity. In the chick embryo however, skeletal deformity can occur in the absence of changes in collagen solubility, and vice versa (1). Since the changes in the functional properties of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

1963
1963
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 13 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…Strong evidence exists that pyridoxal phosphate is also necessary as a cofactor of lysyl oxidase (Levene, 1961a). Reagents which react with carbonyl groups [e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Strong evidence exists that pyridoxal phosphate is also necessary as a cofactor of lysyl oxidase (Levene, 1961a). Reagents which react with carbonyl groups [e.g.…”
mentioning
confidence: 99%
“…phenylhydrazine, hydroxylamine (Harris et al, 1974), isoniazid (Arem & Misiorowski, 1976)] all inactivate the enzyme. Experiments in vivo with chicks have shown that inhibition of lysyl oxidase by a pyridoxinedeficient diet (Murray et al, 1978) or by lathyrogens (Levene, 1961a) can be reversed by pyridoxal or pyridoxine. Other aldehydes were less effective in reversing the effects of lysyl oxidase inhibition (Levene, 1961a).…”
mentioning
confidence: 99%
“…In the chick embryo, isoniazid has been shown to alter the collagen content and produce a lathyrogenic effect that is reversible by pyridoxal (32). Finally, the association of cutis laxa with allergic reactions to penicillin and with multiple myeloma raises the question of an immune-mediated mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Goltz et al (11) suggested that altered copper metabolism may be the primary defect in cutis laxa and an abnormality in serum copper may lead to dysfunction of a serum eiastase itihibitor. In the chick embryo, isoniazid has been shown to alter the collagen content and produce a lathyrogenic effect that is reversible by pyridoxal (32). Finally, the association of cutis laxa with allergic reactions to penicillin and with multiple myeloma raises the question of an immune-mediated mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The compound which resolved the problem was isonicotinic acid hydrazide (isoniazid, INAH) which proved to be a lathyrogen (Levene, 1961a). As a result, lathyrogenic compounds fell, on an equimolar basis, into four groups of diminishing potency:…”
mentioning
confidence: 99%